BRAZILIAN NSDI TEN YEARS LATER: CURRENT OVERVIEW, NEW CHALLENGES AND PROPOSITIONS FOR NATIONAL TOPOGRAPHIC MAPPING - Silva, Leonardo Scharth Loureiro; Camboim, Silvana Philippi (Boletim de Ciências Geodésicas, 2021)
Cartographic data represents the main and basic component of a Spatial Data Infrastructure. SDI, in turn, has the role of supporting, with strategic information, the most diverse political and economic actions, in the management and planning of public actions. Thus, this work aims, initially, to present an overview of cartography in Brazil through the analysis of the evolution of topographic mapping coverage in the country. For each of the main scales used, a coverage map was created. The analyzes reflect three different periods (until 1997, between 1998 and 2007, after 2008) in order to relate how and to what degree, the creation of Brazilian National SDI (in 2008) had an impact on the mapping production in the country. Given the current panorama, as a final objective, this paper aims at to present proposals to leverage the coverage of this reference data. One of them is the use of new data sources such as Volunteered Geographic Information, especially in areas with outdated mapping or without mapping, as has already been used in some countries. Another proposition is to share the responsibility of mapping through partnerships with other levels of government, which would result the decentralization and the optimization of cartographic production.